Pengaruh Akuntabilitas, Conflict of Interest dan Komitmen Organisasi terhadap Fraud Pengelolaan Dana BLT pada Masa Pandemic COVID-19 - Pamungkas, Bintang; Helmayunita, Nayang; Honesty, Fiola Finomia (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to determine the effect of accountability, conflict of interest and organizational commitment to fraud in managing BLT funds during the Covid-19 pandemic. The population of this study were all village officials in the Air Pura sub-district. The sample used was 59 respondents with total sampling technique. This study used a quantitative method by distributing questionnaires directly. This study was tested using multiple regression analysis. The results obtained from this study indicate that accountability and conflict of interest did not have a significant effect on BLT fund management fraud during the Covid-19 pandemic, while organizational commitment had a positive and significant effect on BLT fund management fraud during the Covid-19 pandemic.